Brain atrophy assessment in multiple sclerosis: importance and limitations. - Giorgio, A; Battaglini, M; Smith, S; De Stefano, N (2008)
The use of MR imaging-derived methods to provide sensitive and reproducible assessments of brain volume (eg, to estimate atrophy) has increased the interest in this measure as a reliable indicator of disease progression in many neurologic disorders, including multiple sclerosis (MS). After an overview of the most commonly used methods for assessing brain atrophy state and changes in MS, this article discusses the clinical relevance of the most recent developments and reflects on its interpretation in a complex disease such as MS. Some caveats of these measurements are considered and possible future approaches discussed for improving the potential of this measure in assessing and monitoring pathologic evolution and treatment efficacy in this disease.